Brand Credibility and Brand Reputation on Brand Performance - Poetry, Keyka; Ardiani, Nadia Rizky; Yuliana, Lingga (Journal of Applied Business Administration, 2025)
With regard to the Wardah brand, this study intends to examine how brand credibility and reputation affect brand performance. In this work, quantitative research methodologies are applied. Purposive sampling is used in the sampling method. This survey included 201 respondents in total. Respondents are Indonesian-born women between the ages of 17 and 55 who use skincare and makeup items under the Wardah brand. Through the use of Google Forms, the data source distributes questionnaires that collect primary data. In this study, closed questions with response options of strongly disagree, disagree, agree, and strongly agree were employed on a Likert scale. Version 4.1.0.0 of the SmartPLS tool is used in the partial least squares data analysis method. According to the study's findings, there is a relationship between brand performance and credibility. A relationship between brand reputation and brand performance is evident from the second hypothesis